(untitled) (Journal of the College of Basic Education, 2023)
This section contained the introduction, which was an introduction to the subject of the study, as well as the research problem, in which the researcher found it appropriate to know the mechanical variables related to the scoring process and the hypothesis on which this study was built, which assumes that there is a relationship between the biokinematic variables and the success of scoring in basketball., as well This chapter dealt with the temporal, spatial and human fields of research.